Occupational Health and Safety for Workers Who Are Disabled in Africa - Chikwanka, Taonga Zoe; Chiluba, Brian Chanda (The Center for Disability Studies and Services Brawijaya University, 2020)
A good working environment or work is very important for global, national and local economic and social development. Legislation and inspection of workplaces is done to help monitor compliance with health and safety agencies and also insure health and safety in workplaces. Occupational health is a multi-disciplinary action that concentrates on protecting and promoting the health of workers by preventing and controlling occupational diseases and accidents. In Africa occupational health also looks at the factors and conditions that are hazardous to the health and safety of workers. Occupational health focuses on enabling workers to conduct socially and economically productive lives and contribute to sustainable development. According to the UN statistics about 300 million people are disabled in Africa. With the increasing number of people living with disability a number of countries have developed laws and regulations that allow disabled people to work. This paper aims at addressing different occupational and health issues which will help understand occupational health, the problems that comes it and how to address those problems. This article will also review the challenges of people living with disability face in employment and how they are treated at their workplaces. This review will be passed on other articles downloaded from google search. 14 articles where downloaded but only 11 where used. The others were excluded because of the limitation on the number of word and pages the review article was supposed to have.